Indian Woman, Port of Spain, Trinidad - (:unkn) unknown (My University, 2008)
Photo of an East Indian woman and child, both in traditional East Indian wear.
Colour: Brown and white; faded Style: Portrait; Other: Bordered, Undivided
Keywords: Postcards; East Indians--Trinidad and Tobago; Women, East Indian--Trinidad and Tobago; Trinidad and Tobago; Saris--India; Ethnic costume--India; Clothing and dress--Trinidad and Tobago; Women's clothing--Trinidad and Tobago; Children--Trinidad and Tobago